1993
DOI: 10.1007/bf00229024
|View full text |Cite
|
Sign up to set email alerts
|

Early development of the SI cortical barrel field representation in neonatal rats follows a lateral-to-medial gradient: an electrophysiological study

Abstract: Development of the barrel field in layer IV of SI cortex of neonatal rats was studied in vivo using electrophysiological recording techniques. This study was designed to determine (a) the earliest time SI cortex is responsive to peripheral mechanical and/or electrical stimulation and (b) whether the development of the SI cortical barrel field map of the body surface follows a differential pattern of development similar to the pattern previously demonstrated using peanut agglutinin (PNA) binding (McCandlish et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…After the second week, cortical processing between distant networks is established with evoked responses invading several cortical networks downstream of S1 in the frontal motor region and in the sensory and motor regions of the other hemisphere. Sensory evoked responses can be elicited in the rat S1 cortex as early as P1 (Armstrong-James, 1975;McCandlish et al, 1993); however, as in newborns of other mammals comprising humans, cortical responses are weaker and slower than in adults (Pihko and Lauronen, 2004;Borgdorff et al, 2007). In agreement, we observed strong reinforcement and drastic acceleration of cortical responses during the postnatal period.…”
Section: Discussionsupporting
confidence: 85%
“…After the second week, cortical processing between distant networks is established with evoked responses invading several cortical networks downstream of S1 in the frontal motor region and in the sensory and motor regions of the other hemisphere. Sensory evoked responses can be elicited in the rat S1 cortex as early as P1 (Armstrong-James, 1975;McCandlish et al, 1993); however, as in newborns of other mammals comprising humans, cortical responses are weaker and slower than in adults (Pihko and Lauronen, 2004;Borgdorff et al, 2007). In agreement, we observed strong reinforcement and drastic acceleration of cortical responses during the postnatal period.…”
Section: Discussionsupporting
confidence: 85%
“…This finding agrees with the late development of functional GABA inhibition (Miles and Wong, 1987;Luhman and Prince, 1991;Agmon et al, 1996). Additionally, evoked electrical responses in barrel cortex are minimal at birth and change markedly in intensity, latency, and complexity during the second and third postnatal weeks (McCandlish et al, 1993;SeoHiraiwa et al, 1995). Electrophysiological studies have also indicated that physiological plasticity persists for several weeks after the barrel field is anatomically immutable (Fox, 1992).…”
Section: Prolonged Maturation Of Somatosensory Cortical Gad Immunoreasupporting
confidence: 82%
“…In the cerebral cortex, the neurogenetic gradient extends from anterolateral toward posterior and medial, in parallel with the rows of barrels in SI (Hicks and D'Amato, 1968;Smart, 1984;Bayer and Altman, 1991;Erzurumlu and Jhaveri, 1992;Bishop et al, 2000). A similar gradient was reported for the development of electrophysiological specificity (McCandlish et al, 1993). Thus, anterolaterally located barrels (high numbers) are developed before the more medially and posteriorly located barrels (low numbers).…”
Section: Establishment Of Corticopontine and Corticostriatal Topographymentioning
confidence: 57%